(3GdeNJUQ GdeajO aj Yde GdJGQjNs - (3eMeO Hf SdjeGf Hf SYO Hf eSYhO GdcGajLj GdQhej GdMfaj, eMjj GdOjf, CHh YHO Gddg, J (B879 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi Ndb GdCQV hGdSeGA heG HjfgG YHQI dChdi Gdfgi s
(3QJHg GdeDda Ydi KdGKI CHhGH ai eHGOF Yde GdJGQjN hCUhdg heSGFdgs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B150s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B114 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B1 - (3U (B239 s
Keywords: (3GdJGQjNs